Asimetri Informasi sebagai Pemoderasi Pengaruh Kekuatan Pasar dan Tekanan Keuangan terhadap Real Earnings Management - Haq, Aqamal; Murwaningsari, Etty (PT. Cendekia Sapta Indonesia, 2025)
This study investigates the impact of financial distress, market power, and information asymmetry on real earnings management (REM) practices in consumer goods companies in Indonesia. The analysis is based on panel data comprising 184 firm-year observations from the consumer cyclical and non-cyclical sectors listed on the Indonesia Stock Exchange during the 2022–2023 period. REM is measured using abnormal cash flow from operations (Abnormal CFO), which refers to deviations in cash flow from normal operating levels, based on the Roychowdhury (2006) model. Financial distress is assessed through the Altman Z-Score, market power is measured using the Herfindahl-Hirschman Index (HHI), and information asymmetry is proxied by the bid-ask spread. The study further explores the moderating role of information asymmetry in the relationship between financial distress, market power, and REM. Data analysis employs a panel data regression using the Random Effects Model, following classical assumption tests and the Breusch-Pagan Lagrange Multiplier (LM) Test. The results reveal that financial distress (Z-Score), information asymmetry (bid-ask spread), the interaction terms of information asymmetry with financial distress (AI_FINDIS) and market power (AI_MS), and firm size have significant effects on REM. In contrast, market power (HHI) and leverage do not exhibit statistically significant effects. These findings suggest that financially healthier firms tend to exhibit greater flexibility in engaging in REM, while information asymmetry serves as a key contextual factor that can either amplify or attenuate the influence of other variables on REM behavior. This study offers a novel contribution by developing the REM Index Plus, which integrates multiple dimensions of real activity manipulation to improve detection accuracy in REM measurement. The results reveal that financial distress (Z-Score), information asymmetry (bid-ask spread), the interaction terms of information asymmetry with financial distress (AI_FINDIS) and market power (AI_MS), and firm size have significant effects on REM. In contrast, market power (HHI) and leverage do not exhibit statistically significant effects. These findings suggest that financially healthier firms tend to exhibit greater flexibility in engaging in REM, while information asymmetry serves as a key contextual factor that can either amplify or attenuate the influence of other variables on REM behavior. This study contributes to the growing body of literature on earnings management in developing economies, particularly Indonesia, and offers practical implications for regulators, auditors, and investors to consider the presence of information asymmetry when evaluating earnings quality